Targeting Muscle-Resident Single Cells Through in vivo Electro-Enhanced Plasmid Transfer in Healthy and Compromised Skeletal Muscle - Florio, Francesca; Accordini, Silvia; Libergoli, Michela; Biressi, Stefano (Frontiers in Physiology, 2022)
Skeletal muscle is composed of syncytial muscle fibers, and by various mononucleated cellular types, such as muscle stem cells, immune cells, interstitial and stromal progenitors. These cell populations play a crucial role during muscle regeneration, and alterations of their phenotypic properties have been associated with defective repair and fibrosis in aging and dystrophic muscle. Studies involving in vivo gene modulation are valuable to investigate the mechanisms underlining cell function and dysfunction in complex pathophysiological settings. Electro-enhanced transfer of plasmids using square-wave generating devices represents a cost-effective approach that is widely used to transport DNA to muscle fibers efficiently. Still, it is not clear if this method can also be applied to mononuclear cells present in muscle. We demonstrate here that it is possible to efficiently deliver DNA into different muscle–resident cell populations in vivo. We evaluated the efficiency of this approach not only in healthy muscle but also in muscles of aging and dystrophic animal models. As an exemplificative application of this method, we used a strategy relying on a reporter gene-based plasmid containing regulatory sequences from the collagen 1 locus, and we determined collagen expression in various cell types reportedly involved in the production of fibrotic tissue in the dystrophic settings. The results enclosed in this manuscript reveal the suitability in applying electro-enhanced transfer of plasmid DNA to mononucleated muscle-resident cells to get insights into the molecular events governing diseased muscle physiology.